As práticas educativas com estudantes dos Anos Iniciais do Ensino Fundamental que apresentam dificuldades de aprendizagem - JOCIANE DE OLIVEIRA NUNES GONÃ ALVES (2021)
The teaching and learning processes are complex and determined by numerous variables. These processes present difficulties derived from teaching, but also with regard to learning. The characteristics of learning difficulties are diverse and from different origins, surpassing what would only be the Target Audience of Special Education (TASE). These difficulties need to be known by the educational institution to plan and by the teacher so that educational practices that serve all students are developed. The educational practices considered here are those that are supported by the paradigm of inclusive education and, consequently, for all students. This research aimed to identify and analyze educational practices with students who have learning difficulties, from the fourth and fifth years of the Initial Years of Elementary School. It is a research with a qualitative approach based on the case study and, methodologically, two stages were organized for its realization. The first stage was bibliographic for the theoretical foundation and the scientific production. The second stage consisted of data collection with document analysis of the Pedagogical Political Project (PPP), lesson plans and multiple questionnaires for fourth and fifth grade teachers and another for the pedagogical direction/coordination) based on organizational topics and strategies of the participants in the development of educational practices. Five categories of analysis derived from the theoretical foundation were built, namely: student recognition; planning; methodologies; resources; and assessments focused on students with difficulties. The results showed that teachers identify learning difficulties, in a very elementary and non-systematized way, and pass this information on to the management team; in this way, in their planning, it is not manifested either, but there is an attempt to include all of them in the methodological proposals and in the resources used to carry out the educational practice. Although neither the definition nor the form of addressing the learning difficulties appears explicitly, it is clear that there is an intention to build inclusive practices, in which it is considered how the student learns, based on the concreteness of the difficulties they present and, also, how educational practices are developed to serve them.